2020
DOI: 10.1002/mrd.23332
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene regulation in selected lines for high and low sperm production in male guppies

Abstract: In species where females mate with more than one male during the same reproductive event, males typically increase the number of sperm produced to boost their fertilization share. Sperm is not limitless, however, and theory predicts that their production will come at the cost of other fitness-related traits, such as body growth or immunocompetence, although these evolutionary trade-offs are notoriously difficult to highlight. To this end, we combined artificial selection for sperm production with a transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…For example, it has been demonstrated that immune‐challenged individuals exhibit reduced reproductive success and that increased investment in reproduction often results in decreased immunocompetence (Adamo, Jensen, & Younger, 2001; Fedorka, Zuk, & Mousseau, 2004; Rolff & Siva‐Jothy, 2002; Schmid‐Hempel, 2003). This trade‐off between immunity and reproduction is also reported specifically for the production of gametes (Devigili, Belluomo, Locatello, Rasotto, & Pilastro, 2017; McNamara, Lieshout, & Simmons, 2014; Radhakrishnan & Fedorka, 2012; Cattelan, Vidotto, Devigili, Pilastro, & Grapputo 2020). However, it is now clear that immunity and reproduction are linked beyond these trade‐offs, as there is evidence, in a wide taxonomic range of species, of a link between immunity and competitive fertilization success, that is when sperm from two or more males compete to fertilize the same set of eggs (Lawniczak et al, 2007; Morrow & Innocenti, 2012).…”
Section: Introductionmentioning
confidence: 56%
“…For example, it has been demonstrated that immune‐challenged individuals exhibit reduced reproductive success and that increased investment in reproduction often results in decreased immunocompetence (Adamo, Jensen, & Younger, 2001; Fedorka, Zuk, & Mousseau, 2004; Rolff & Siva‐Jothy, 2002; Schmid‐Hempel, 2003). This trade‐off between immunity and reproduction is also reported specifically for the production of gametes (Devigili, Belluomo, Locatello, Rasotto, & Pilastro, 2017; McNamara, Lieshout, & Simmons, 2014; Radhakrishnan & Fedorka, 2012; Cattelan, Vidotto, Devigili, Pilastro, & Grapputo 2020). However, it is now clear that immunity and reproduction are linked beyond these trade‐offs, as there is evidence, in a wide taxonomic range of species, of a link between immunity and competitive fertilization success, that is when sperm from two or more males compete to fertilize the same set of eggs (Lawniczak et al, 2007; Morrow & Innocenti, 2012).…”
Section: Introductionmentioning
confidence: 56%
“…We established a panel of four non-VCN candidate genes on four different linkage groups (LG) of the guppy genome: the MC1R itself on LG3, the intermediate filament protein ON3-like on LG2, an uncharacterized protein on LG1 and the β actin on LG 8. The intermediate filament protein and the uncharacterized protein showed similar expression in high and low sperm guppy selected lines (Cattelan, Vidotto, et al, 2020), while the β actin is usually used as a housekeeping gene in gene expression analysis (e.g., Zhang et al, 2023). Locus ID, primers sequences and RT-qPCR profiles are reported in Table S1.…”
Section: Nonvariable Copy Reference Gene Assessmentmentioning
confidence: 99%